Angelologiczny traktat filmowy pomiędzy sztukami. O "Niebie nad Berlinem" Wima Wendersa - Lisiecka, Katarzyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2010)
The study titled Angelologic treatise between the arts. On “The Wings of Desire” by Wim Wenders undertakes to analyze aesthetic and cultural contexts which have impinged on the overall significance of the film. Commencing with the presentation of the angelic motifs and the relations they bear to the angelologic tradition of Western culture, the author identifies some thematic and formal elements which influenced the original concept of spiritual reality depicted in Wenders’s film. Due to its consistent fictional and artistic vision, the picture has been dubbed “the angelologic film treatise”. The second part of the article focuses on the analysis of the visual and musical aspects of the film. The most significant interpretative framework revolves around the concept of visual games and the topos of musical harmony (musica mundana, humana and instrumentalis). The issues under consideration demonstrate the great significance all the formal devices, both in terms of presented images and music, have in constructing deep layers of meaning. A particular importance should be assigned to these audio-visual elements that underscore the relevance of spiritual and existential aspects, constituting the substance of Wenders’s film.
Keywords: Film and music; Musca mundana; Musica humana; Musica instrumentalis